2000
DOI: 10.1161/01.cir.101.15.1867
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Activation by Pore-Forming Structures

Abstract: These findings suggest that transmembrane pore-forming proteins, as a class of molecules, activate ECs through the autocrine effects of IL-1alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 28 publications
2
73
0
Order By: Relevance
“…For example, exposure of endothelial cells to TNF-␣ induces IB, which inhibits NFB activation (31). Consistent with this possibility, Saadi et al (32) found that complement activation on endothelial cells also induces IB expression. The third mechanism involves the up-regulation of protective proteins and pathways in response to a noxious agonist providing cells or tissues of a graft with a general resistance to the initial agonist as well as other unrelated stimuli.…”
Section: Accommodation Of the Graftmentioning
confidence: 81%
“…For example, exposure of endothelial cells to TNF-␣ induces IB, which inhibits NFB activation (31). Consistent with this possibility, Saadi et al (32) found that complement activation on endothelial cells also induces IB expression. The third mechanism involves the up-regulation of protective proteins and pathways in response to a noxious agonist providing cells or tissues of a graft with a general resistance to the initial agonist as well as other unrelated stimuli.…”
Section: Accommodation Of the Graftmentioning
confidence: 81%
“…In addition to mechanical injury, both hypoxia and sublytic complement deposition, which are stimuli relevant to solid organ transplantation, can induce EC release of IL-1␣ (70,71). Sublytic complement deposition allows for IL-1␣ release, independent of cell death, through disruption of the plasma membrane, either by generating membrane pores or by inducing membrane vesiculation (72,73). Also, inflammatory cytokines such as TNF and IL-1 itself cause EC to present bioactive IL-1␣ on their surface in a membrane-bound form (35).…”
Section: Discussionmentioning
confidence: 99%
“…First, MAC has been shown to cause proliferation of glomerular mesangial, endothelial, and epithelial cells in vitro and therefore may be directly involved in inducing a increase in intrinsic cell number (17,21,44,45). Additionally, there are data indicating that MAC can induce the synthesis and/or secretion of a number of proinflammatory cytokines such as TNF-␣ and IL-1 (22,44), adhesion molecules such as ICAM-1 and E selectin (23), and chemokines such as IL-8 (46) and that these effects may play a role in the infiltration of cells to the glomerulus. We have also demonstrated that later in the progression of ANTN, mCd59a deficiency, by allowing unregulated MAC deposition, exacerbates glomerular thrombosis.…”
Section: Discussionmentioning
confidence: 99%